Uchwycić nieuchwytne. Paradoks filmów o free improvised music - Lichota, Patryk (Humaniora. Czasopismo Internetowe, 2025)
The article explores the paradox of representing free improvised music in film – a form defined by transience, dialogue, and the unpredictability of sound. The author outlines the conceptual foundations of this practice, referring to the work of Cornelius Cardew, the Scratch Orchestra and AMM, as well as to Derek Bailey, for whom improvisation was not only a musical method but also a way of thinking and responding to the world. The discussion focuses on the challenge of capturing what is inherently ephemeral and relational. The analysis includes films such as Amplified Gesture (dir. Phil Hopkins), Touch the Sound (dir. Thomas Riedelsheimer), and Step Across the Border (dir. Nicolas Humbert, Werner Penzel), which employ different strategies to convey the processual nature of improvisation. The article argues that while recording inevitably flattens the live interplay between performers, audience, and space, the cinematic medium can simultaneously open new modes of participating in the experience of improvisation.